1992
DOI: 10.1007/bf00226531
|View full text |Cite
|
Sign up to set email alerts
|

Allelic mutations in acetyl-coenzyme A carboxylase confer herbicide tolerance in maize

Abstract: The genetic relationship between acetyl-coenzyme A carboxylase (ACCase; EC 6.4.1.2.) activity and herbicide tolerance was determined for five maize (Zea mays L.) mutants regenerated from tissue cultures selected for tolerance to the ACCase-inhibiting herbicides, sethoxydim and haloxyfop. Herbicide tolerance in each mutant was inherited as a partially dominant, nuclear mutation. Allelism tests indicated that the five mutations were allelic. Three distinguishable herbicide tolerance phenotypes were differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…These isozymes have significant difference in herbicide resistance (18). The studies of ACCase mutants with different sensitivities to herbicides suggested the presence of three, and possibly five, alleles of maize ACCase structural genes (29). These findings show that the isozymes of the eukaryote form are in different cell compartments in Proc.…”
Section: Resultsmentioning
confidence: 77%
“…These isozymes have significant difference in herbicide resistance (18). The studies of ACCase mutants with different sensitivities to herbicides suggested the presence of three, and possibly five, alleles of maize ACCase structural genes (29). These findings show that the isozymes of the eukaryote form are in different cell compartments in Proc.…”
Section: Resultsmentioning
confidence: 77%
“…Similar relationships between whole-plant responses and enzyme activity have been reported for resistant and susceptible Festuca spp. (Stoltenberg et al, 1989) and resistant corn lines derived from tissue culture (Parker et al, 1990;Marshall et al, 1992). This provides strong evidence in support of a single site of action at the enzyme level.…”
Section: Membrane Response and Herbicide Phytotoxicitymentioning
confidence: 63%
“…In a biotype of Italian rygrass (Lolium multiflorum) that was selected with an AOPP herbicide, the ACCase is resistant to AOPP but not CHD herbicides (Gronwald 1991). Maize cell cultures that were selected with sethoxydim or haloxyfop developed resistance as a consequence of mutations of the gene coding for ACCase (Marshall et al 1992), with modified forms of the enzyme encoded by different allelic mutations at the same locus. These data, together with the L. rigidum data herein, show that several modifications of ACCase, endowing resistance to CHD andor AOPP herbicides, are possible and that the pattern of cross-resistance is determined by the type of mutation.…”
Section: Inhibition Of Accase By Herbicides the Activity Ofmentioning
confidence: 99%